How can neuroscience inform our coaching practice – six strategies to facilitate an optimal brain state in coachees. Issue 4 (1st July 2019) - Bamber, Rachel
Abstract : Purpose: How do you ensure that your coachees are getting the most value, support, and challenge from your coaching sessions? Before you even start asking questions and engaging in a coaching conversation, neuroscience can help you! The purpose of this paper is to outline six easy strategies that you can deploy to enable the best brain state to aid cognition, decisions, and creative thinking for your coachee and yourself. Design/methodology/approach: A viewpoint based on the latest research from neuroscience and the author's expertise as a coach for over 15 years. Findings: Using the latest research from neuroscience to assist coachees to find their own solutions to the issues they face ensures they take ownership and are more motivated to take action. Originality/value: The paper takes key elements from the latest evidence in neuroscience and applies them to the practice of coaching.